2018
DOI: 10.1016/j.jviromet.2018.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Viral interference between low pathogenic avian influenza H9N2 and avian infectious bronchitis viruses in vitro and in ovo

Abstract: It appears that either AIV or IBV has a negative impact on the other virus growth when they are inoculated simultaneously or sequentially. The ELISA results showed that higher level of secreted IL-1beta varies, depending on the viral interference conditions between both viruses, during mixed infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
0
9
2
1
Order By: Relevance
“…while other co-infection groups had conditional effects on the proliferation of PPRV and GTPV. This suggested that the two viruses competitively proliferate when inoculated on GSF cells, which was quite different from the results of other studies on viral interference [ 36 ]. Other studies found that under co-infection with PCV2 and Gram-negative bacteria, AIV, and NDV, the replication of only one virus was reduced [ 37 , 38 ].…”
Section: Discussioncontrasting
confidence: 94%
“…while other co-infection groups had conditional effects on the proliferation of PPRV and GTPV. This suggested that the two viruses competitively proliferate when inoculated on GSF cells, which was quite different from the results of other studies on viral interference [ 36 ]. Other studies found that under co-infection with PCV2 and Gram-negative bacteria, AIV, and NDV, the replication of only one virus was reduced [ 37 , 38 ].…”
Section: Discussioncontrasting
confidence: 94%
“…H9N2 is important due to its widespread circulation in domestic poultry, especially in the presence of other co-infecting pathogens. For example, co-infection with E. coli and H9N2 could cause more serious synergistic pathogenic effects, indicating the role of both pathogens as complicating factors in poultry infections [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on in vitro and in ovo interference between AIV and IBV-H120 using, respectively, cultured chicken embryo lung cells and embryonated SPF eggs, have shown that the second inoculated virus slows down the process of viral replication of the first administered one [36]. At the same age, groups simultaneously infected had numerically lower antibody titers as compared to groups singly or sequentially infected.…”
Section: Discussionmentioning
confidence: 93%